Public relations expenditure, media tone, and regulatory decisions - Wu, Yanling; Tian, Gary Gang (Journal of Corporate Finance, 2021)
This paper examines whether and how firms influence regulatory decisions through media capture. Using the unique Chinese regulation setting, we find that higher public relations expenditure reduces a negative pre-IPO media tone and this relationship is weaker when both firms and media outlets face higher legal punishment risks. By linking the incentives for media capture to regulatory decisions, we further find that a less negative media tone is associated with a higher likelihood of IPO approval. In sum, our findings document that firms can capture media tone and, thus, obtain preferred IPO approvals from regulators, which in turn reduces resource allocation efficiency in an emerging market.